Implementasi Resource Assignement Algorithm Pada Aplikasi Bahasa Latin Flora Dan Fauna Untuk Pelajar Berbasis Android - Wijaya, Ardi; Sahputra, Eka; Kornengsih, Resnita (UNIVED Press, 2020)
Several studies state that there are problems that arise from excessive gaming activities, these problems are losing control over time and experiencing difficulties in academic matters. To foster students' enthusiasm for learning, teachers are required to make learning more interesting and innovative, efforts to achieve interesting and innovative learning are by using learning media. The difficulty of learning Latin makes children less interested because it uses language that is difficult to understand and pronounce. Utilizing mobile devices as a medium for learning makes it easy for students to learn practically anytime and anywhere using mobile. Resource Assignment Algorithm (RAA) has the ability to produce a value based on several existing values ​​sorted using a priority scale. In its application, the application of the introduction of Latin flora and fauna for junior high school students will produce a value for executing a decision for students in answering a question from learning Latin flora and fauna. Based on system testing with User Staticfaction Testing, the results showed 72% were very interesting, 21% were interesting and 7% were not interesting. These results show that the application design is good and suitable for use